Eotaxin-1/CCL11 promotes cellular senescence in human-derived fibroblasts through pro-oxidant and pro-inflammatory pathways - Lavandoski, Patrícia; Pierdoná, Vinícius; Maurmann, Rafael Moura; Grun, Lucas Kich; Guma, Fatima T. C. R.; Barbé-Tuana, Florencia María (Frontiers in Immunology, 2023)
Eotaxin-1/CCL11 is a pivotal chemokine that plays a crucial role in eosinophil homing to the lungs of asthmatic patients. However, recent studies suggest that CCL11 is also involved in the aging process, as it is upregulated in various elderly diseases, and is correlated with shorter telomere length in leukocytes from child asthmatic patients. Despite its potential pro-aging effects, the precise contribution of CCL11 and the underlying mechanisms involved in the promotion of cellular senescence remains to be fully understood. Therefore, the primary objective of this study was to explore the role of CCL11 on senescence development and the signaling pathways activated by this chemokine in lung fibroblasts. Using in silico, in vitro, and ex vivo approaches, we demonstrate that eotaxin-1/CCL11 promotes a pro-oxidative and pro-inflammatory response that ultimately leads to cellular senescence in human embryonic lung fibroblasts. Furthermore, our data show that airway epithelial lung cells from atopic asthma patients overexpress aging markers such as CDKN2A (p16INK4a) and SERPINE1. These findings provide new insights into the mechanisms underlying the pro-aging effects of CCL11 in the lungs of asthma-committed individuals. Understanding the role of CCL11 on senescence development may have important implications for the treatment of agerelated lung diseases and asthma.